EFFECT OF 4-BUTANOLIDES ON THE PROCESS OF BIOSYNTHESIS AND DECAY OF MEMBRANE GLYCEROLIPIDS AT IONIZING IRRADIATION (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
The activity of systems of several enzymes biosynthesis of membrane glycerolipids in lung tissues at ionizing irradiation is studied. It is revealed that irradiation brings a sharp decrease of glycerokinase and cytoplasmatic and mytochondrial glycerophosphat dehydrogenase in lungs. In those conditions, the activity of phospholipase A2 is sharply increased in the mentioned tissue, which gives evidence about the speed of membrane phosphatides-glycerides degradation. The application of 4-butanolides is accompanied with processes of glicerokinases and glicolitics ways of phosphatidogeneses in the mentioned tissue during ionizing irradiation.